2014
DOI: 10.1088/1674-1056/23/12/127104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GaN cap layer thickness on an AlN/GaN heterostructure

Abstract: Effects of GaN cap layer thickness on an AlN/GaN heterostructure * Zhao Jing-Tao(赵景涛) a) , Lin Zhao-Jun(林兆军) a) † , Luan Chong-Biao(栾崇彪) a) , Lü Yuan-Jie(吕元杰) b) , Feng Zhi-Hong(冯志宏) b) , and Yang Ming(杨 铭) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Heikman et al [11] and Asgari et al [12] have proposed a GaN/Al0.32Ga0.68N/GaN heterostructure deposited on a sapphire substrate, and they show that the sheet carrier density decreases with thicker cap layers while the mobility increases. Similar effects were reported by Tao et al [13] for an AlN/GaN heterostructure. To maximize the high frequency performance of AlGaN HEMTs, Green et al [14] incorporated GaN cap layers in GaN/AlGaN/GaN structures by heavily n-doping the upper GaN layer; thus parasitic contact resistances were greatly reduced.…”
Section: Introductionsupporting
confidence: 89%
“…Heikman et al [11] and Asgari et al [12] have proposed a GaN/Al0.32Ga0.68N/GaN heterostructure deposited on a sapphire substrate, and they show that the sheet carrier density decreases with thicker cap layers while the mobility increases. Similar effects were reported by Tao et al [13] for an AlN/GaN heterostructure. To maximize the high frequency performance of AlGaN HEMTs, Green et al [14] incorporated GaN cap layers in GaN/AlGaN/GaN structures by heavily n-doping the upper GaN layer; thus parasitic contact resistances were greatly reduced.…”
Section: Introductionsupporting
confidence: 89%
“…The decrease in ns led to a reduction in the intensity of roughness scattering at the heterojunction interface [18,19]. In addition, as the cap thickness increased, the surface roughness of these samples decreased and the distance from the 2DEG to the surface of the epitaxial layer increased, which may lead to a decrease in remote scattering intensity from the surface charges [20,21]. In addition, the difference in µH between the sample with a 3 nm cap and the sample with a 5 nm cap was Figure 3 shows the values of 2DEG mobility (µ H ), 2DEG density (n s ), and sheet resistance (R s ) of samples with cap thicknesses of 0, 1, 3, and 5 nm measured at 300 K. As the cap thickness increased from 0 nm to 5 nm, the n s decreased from 1.13 × 10 13 cm −2 to 1.02 × 10 13 cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in n s led to a reduction in the intensity of roughness scattering at the heterojunction interface [18,19]. In addition, as the cap thickness increased, the surface roughness of these samples decreased and the distance from the 2DEG to the surface of the epitaxial layer increased, which may lead to a decrease in remote scattering intensity from the surface charges [20,21]. In addition, the difference in µ H between the sample with a 3 nm cap and the sample with a 5 nm cap was observed to be nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
“…18,20 A computational study further confirmed that introducing Zn on β-Ga 2 O 3 can enhance the absorption and reflectivity of β-Ga 2 O 3 in the near infrared region. 23 However, more than half of the studies summarizing in Table S1† are experimental works, containing various photocatalytic reactions, such as hydrogen production, CO 2 reduction, and harmful volatile organic compounds removal. Moreover, only a few dopant types were studied.…”
Section: Introductionmentioning
confidence: 99%